Identification of drivers, benefits, and challenges of ISO 50001 through case study content analysis. (July 2020) - Fuchs, Heidi; Aghajanzadeh, Arian; Therkelsen, Peter
Abstract: An expanding body of research is defining drivers, benefits, and challenges of adopting ISO 50001 energy management systems. The Clean Energy Ministerial's Energy Management Leadership Awards program requires ISO 50001-certified organizations to develop case studies of their implementation experience. 72 recent case studies spanning multiple economic sectors provide a unique global look at implementation from certified organizations' perspectives. This dataset was investigated through content analysis of phrases related to motivations and goals, the role of management and the organization, benefits achieved, keys to success, and challenges. This paper presents findings from this quantitative analysis of "codes" assigned to phrases that capture their meaning. While organizations adopted ISO 50001 for different motives and saw myriad benefits beyond energy savings and associated greenhouse gas emissions reductions, commonalities exist. The most frequently identified drivers are existing values and goals, environmental sustainability, and government incentives or regulations. Findings also include: obtaining and sustaining top management support is critical; top benefits mentioned are cost savings, productivity, and operational improvements; and the primary barrier is lacking a culture of energy management. Policymakers and others looking to accelerate ISO 50001 uptake can use these findings to highlight benefits and incentives that will resonate with corporate decisionmakers worldwide. Highlights: Content analysis is a novel approach for analyzing ISO 50001 case studies. Outreach should target management and organizations with an existing energy vision. Government regulations or incentives are important factors in pursuing ISO 50001. Management support and an energy-aware culture are among top keys to success. Challenges include lack of energy-focused culture, data, and in-house expertise.